2013
DOI: 10.1111/lam.12033
|View full text |Cite
|
Sign up to set email alerts
|

Successional colonization of perennial ryegrass by rumen bacteria

Abstract: Significance and Impact of the Study: We investigated, over a 24-h period in sacco, whether attachment of rumen microbiota to perennial ryegrass (PRG) showed successional changes in diversity. Knowledge of the bacterial species that attach to PRG over time may aid our understanding of the temporal function of the attached microbiota and ultimately permit the development of novel strategies for improving animal production to meet the future demands for meat and milk. AbstractThis study investigated successiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 32 publications
4
51
1
Order By: Relevance
“…Prevotella is one of the most predominant bacterial genera found in the rumen, accounting for up to 20 % of the total bacteria found in sheep (Bekele et al 2010), between 14 and 60 % in dairy cows (Kong et al 2010; Stevenson and Weimer, 2007) and up to 90 % in steers (Huws et al 2010; 2013). The publication of the P. ruminicola 23 and Prevotella bryantii B(1)4 genomes (Purushe et al 2010) may explain why most of the fosmid sequences were similar to these entries as only limited information on other rumen bacteria is currently deposited.…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella is one of the most predominant bacterial genera found in the rumen, accounting for up to 20 % of the total bacteria found in sheep (Bekele et al 2010), between 14 and 60 % in dairy cows (Kong et al 2010; Stevenson and Weimer, 2007) and up to 90 % in steers (Huws et al 2010; 2013). The publication of the P. ruminicola 23 and Prevotella bryantii B(1)4 genomes (Purushe et al 2010) may explain why most of the fosmid sequences were similar to these entries as only limited information on other rumen bacteria is currently deposited.…”
Section: Discussionmentioning
confidence: 99%
“…Primary colonisers attach to newly ingested forage particles, exude extracellular polymeric substances and then develop into biofilm colonies on perennial ryegrass leaf, for instance, in less than 1 h (Huws et al 2013). Bacteria have evolved signalling mechanisms that enable them to communicate and co-ordinate their activities so that they can respond quickly to environmental changes (such as establishment of nearby bacteria or the presence of nutrients or toxins); they exhibit a wide range of interactive, multicellular behaviors such as dispersal, nutrient acquisition, biofilm formation and quorum sensing (West et al 2006).…”
Section: The Importance Of Rumen Microbial Ecologymentioning
confidence: 99%
“…Previous studies have shown temporal changes in bacterial (Edwards et al, 2007; Huws et al, 2013) and fungal (Edwards et al, 2008) populations during ruminal incubation of fresh perennial rye grass ( Lolium perenne ). Specifically, these studies revealed a rapid colonization of the plant material within 5 min of rumen-incubation by both bacterial (Edwards et al, 2007) and fungal populations, followed by a compositional shift in bacterial populations between 2 and 4 h following incubation (Huws et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown temporal changes in bacterial (Edwards et al, 2007; Huws et al, 2013) and fungal (Edwards et al, 2008) populations during ruminal incubation of fresh perennial rye grass ( Lolium perenne ). Specifically, these studies revealed a rapid colonization of the plant material within 5 min of rumen-incubation by both bacterial (Edwards et al, 2007) and fungal populations, followed by a compositional shift in bacterial populations between 2 and 4 h following incubation (Huws et al, 2013). Compositional dynamics may vary among forage types based on observed differences in fiber disappearance and fibrolytic enzyme activities (Bowman and Firkins, 1993) and the observed temporal changes in microbiota may be affected by residual plant metabolism of fresh forages (Huws et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation